A crise e a fragmentação da psicologia: uma visão do pensamento complexo - Santos, Murillo Rodrigues dos (2016)
This study aims to present a view of Complex Thought about the themes of crisis and fragmentation of psychology as a science and profession. Therefore, we carried out a literature review of the important concepts of Complex Thought in regards to the relationship with the subject, specifically related to epistemology, ontology, method and methodology. After presented the theoretical framework and method that support this work, it elaborates on the results achieved through reflections raised by the collected bibliography. Thus, it carried out an interpretative analysis of the senses historically attributed to the concepts of "crisis" and "fragmentation", by building units of senses/analysis in order to propose a new reading possible for the subject, understanding the crisis and fragmentation not as diversity of theoretical positions or the difficulty of finding an unique position/object/language, but as the inability to recognize itself while a polysystemic and plural science.